Characterization and rank assignment criteria for the anaerobic fungi (Neocallimastigomycota). Issue 7 (19th July 2022) - Elshahed, Mostafa S.; Hanafy, Radwa A.; Cheng, Yanfen; Dagar, Sumit S.; Edwards, Joan E.; Flad, Veronika; Fliegerová, Kateřina Olša; Griffith, Gareth W.; Kittelmann, Sandra; Lebuhn, Michael; O'Malley, Michelle A.; Podmirseg, Sabine Marie; et al.
Abstract : Establishing a solid taxonomic framework is crucial for enabling discovery and documentation efforts. This ensures effective communication between scientists as well as reproducibility of results between laboratories, and facilitates the exchange and preservation of biological material. Such framework can only be achieved by establishing clear criteria for taxa characterization and rank assignment. Within the anaerobic fungi (phylum Neocallimastigomycota), the need for such criteria is especially vital. Difficulties associated with their isolation, maintenance and long-term storage often result in limited availability and loss of previously described taxa. To this end, we provide here a list of morphological, microscopic, phylogenetic and phenotypic criteria for assessment and documentation when characterizing newly obtained Neocallimastigomycota isolates. We also recommend a polyphasic rank-assignment scheme for novel genus-, species- and strain-level designations for newly obtained Neocallimastigomycota isolates.